2017
DOI: 10.5565/rev/qpsicologia.1377
|View full text |Cite
|
Sign up to set email alerts
|

Psychology Students’ learning strategies: An exploratory study

Abstract: ResumoNeste estudo objetivamos caracterizar as estratégias de aprendizagem utilizadas por estudantes de primeiro a quarto ano de graduação em Psicologia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
2
0
2
Order By: Relevance
“…As this scale assesses the value that students attribute to the educational institution, the importance they assign to accomplishing educational goals successfully, the results showed that students seem to value coursework and academic performance as a means to attain future professional success. This result is positive and is similar to those found by Bartalo and Guimarães (2008) and Endo et al (2017); however, it differs from the results of Iqbal et al (2010), who found that Pakistani university students did not show positive attitudes toward the university.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…As this scale assesses the value that students attribute to the educational institution, the importance they assign to accomplishing educational goals successfully, the results showed that students seem to value coursework and academic performance as a means to attain future professional success. This result is positive and is similar to those found by Bartalo and Guimarães (2008) and Endo et al (2017); however, it differs from the results of Iqbal et al (2010), who found that Pakistani university students did not show positive attitudes toward the university.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, research suggests that university students need to become more proactive, strategic, and self-regulated lifelong learners so they can meet the demands of global economy and modern workforce in rapid evolution (see Pew Research Center, 2016; Weinstein and Acee, 2018). Nevertheless, as the need for greater knowledge, skills, and adaptability in the workforce has increased, the number of students admitted to higher education without appropriate skills to learn has also increased (Bembenutty, 2011;Marini and Boruchovitch, 2014;ACT, 2016;Pavesi and Alliprandini, 2016;Endo et al, 2017;Medeiros and Bittencourt, 2017;Biwer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Learning strategies are part of the psychoeducational research agenda in Brazil. However, there is a higher prevalence of studies focused on elementary school Fluminhan & Murgo, 2019;Oliveira et al, 2020;Suehiro et al, 2018;Trassi et al, 2019) and higher education (Boruchovitch et al, 2020;Endo et al, 2017;Oliveira et al, 2019). Therefore, research aimed at examining the learning strategies of high school students is still incipient in the country.…”
Section: Learning Strategies: Defining the Constructmentioning
confidence: 99%
“…Pesquisas sugerem que os estudantes universitários precisam tornar-se estudantes mais proativos, estratégicos e autorregulados ao longo da vida, para que possam atender às demandas da Economia global e da força de trabalho moderna em rápida evolução (Pew Research Center, 2016;Weinstein & Acee, 2018). No entanto, à medida que aumenta a necessidade de maiores conhecimentos, de habilidades e de adaptabilidade na força de trabalho, o número de alunos que chegam ao Ensino Superior sem habilidades adequadas para aprender também aumenta (ACT, 2016;Bembenutty, 2011;Biwer et al, 2020;Endo et al, 2017;Medeiros & Bittencourt, 2017;Pavesi & Alliprandini, 2016).…”
Section: Apresentaçãounclassified
“…e doEndo et al (2017), que encontraram pontuações mais baixas na escala de autoteste. Diferem, também dos deBartalo e Guimarães (2008) em que os menores escores no LASSI surgiram na escala de gerenciamento do tempo, dos deGanda (2016) em que os menores escores ocorreram na escala de motivação e deIqbal (2010) nos quais os menores escores foram na escala de atitude.…”
unclassified